The impact of price shock of palm oil and rubber toward economy growth of Malaysia / Muhammad Naim Shaharudin and Nor Amalina Ismail - Shaharudin, Muhammad Naim; Ismail, Nor Amalina (Faculty of Plantation and Agrotechnology, 2018)
Palm oil currently is the most consumed edible oil the world, with Malaysia and Indonesia being top two producers in the world, however the changes to oil palm as the main commodity in Malaysia had decreased the contribution and total number of estate rubber in Malaysia. The price shocks may affect the health of the Malaysian economy since Malaysia is a net exporter of the two commodities. Therefore, the current research aims to examine whether the prices of these commodities affect the economic growth of Malaysia both in the long run and short run. The data collected within 36 years (1980-2016) for price of oil palm, price of rubber and annual economy growth of Malaysia from Malaysia Palm Oil Board (MPOB). The data been analyzed by E-Views through unit root and co-integration test. The result of the research reveals that both variable only has short run relationship toward economy growth and from co- integration test show price of palm oil has positive relationship and statistically significant and affected the economy growth, meanwhile from Granger Causality Test show that price of rubber affected the Malaysian economy growth and the result is significant. The conclusion can be drawn that price shock on palm oil and rubber price will affected the economy growth of Malaysia.